GEREJA DAN KRISIS SAMPAH: TANGGUNG JAWAB EKOLOGIS KRISTEN DALAM PENGELOLAAN SAMPAH - Reiny Moniaga; Denny Adri Tarumingi (EKKLESIA: Jurnal Teologi dan Pendidikan Kristiani, 2026)
Abstract: The waste crisis has become one of the most pressing environmental issues in modern society, contributing to ecosystem degradation and declining quality of human life. This problem is not only ecological in nature but also touches on the moral and spiritual dimensions of humanity in its relationship with God’s creation. This article aims to examine the theological responsibility of the church in responding to the waste crisis as part of its faith calling to care for God’s creation. This study employs a qualitative method with a literature review approach, analyzing various theological sources, ecological literature, and biblical texts related to the concepts of creation and human stewardship of the earth. The findings reveal that the Bible affirms humanity’s mandate to cultivate and care for the earth, as stated in Genesis 2:15, which serves as the theological foundation for both human and ecclesial responsibility in preserving the environment. The church is called to foster ecological awareness among its members through faith teaching and concrete actions in waste management and environmental conservation. This contribution is expressed through educational efforts that promote ecological consciousness, as well as practical initiatives such as waste management, plastic reduction, and environmental preservation activities. These efforts not only impact the congregation but also provide benefits to the surrounding community. Therefore, concern for waste issues becomes a form of faith witness that embodies the values of the Kingdom of God in social and ecological life. In this way, caring for waste is not merely an environmental concern but an integral part of the church’s mission to care for God’s creation and to manifest the values of God’s Kingdom in the world. Abstrak: Krisis sampah merupakan salah satu persoalan lingkungan yang semakin serius dalam kehidupan masyarakat modern dan berdampak pada kerusakan ekosistem serta kualitas hidup manusia. Persoalan ini tidak hanya berkaitan dengan aspek ekologis, tetapi juga menyentuh dimensi moral dan spiritual manusia dalam relasinya dengan ciptaan Allah. Artikel ini bertujuan untuk mengkaji tanggung jawab teologis gereja dalam merespons krisis sampah sebagai bagian dari panggilan iman untuk merawat ciptaan Allah. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan yang menganalisis berbagai sumber teologi, literatur ekologi, serta teks Alkitab yang berkaitan dengan konsep penciptaan dan penatalayanan manusia terhadap alam. Hasil kajian menunjukkan bahwa Alkitab menegaskan mandat manusia untuk mengusahakan dan memelihara bumi sebagaimana dinyatakan dalam Kitab Kejadian 2:15, yang menjadi dasar teologis bagi tanggung jawab manusia dan gereja dalam menjaga kelestarian lingkungan. Gereja dipanggil untuk menumbuhkan kesadaran ekologis di tengah jemaat melalui pengajaran iman serta tindakan nyata dalam pengelolaan sampah dan pelestarian lingkungan. Kontribusi tersebut diwujudkan melalui pengajaran yang membangun kesadaran ekologis serta tindakan konkret seperti pengelolaan sampah, pengurangan plastik, dan kegiatan pelestarian lingkungan. Upaya ini tidak hanya berdampak bagi jemaat, tetapi juga memberi manfaat bagi masyarakat sekitar. Sehingga, kepedulian terhadap sampah menjadi bentuk kesaksian iman yang menghadirkan nilai-nilai Kerajaan Allah secara nyata dalam kehidupan sosial dan ekologis. Oleh karena itu, kepedulian terhadap persoalan sampah merupakan bagian dari kesaksian iman gereja dalam merawat ciptaan Allah dan menghadirkan nilai-nilai Kerajaan Allah di tengah dunia.